Die KOMFOR-Studie zum studentischen Wahlverhalten in überfachlichen Studienprogrammen – statistische Analysen und Auswertung von Interviews. - Strunz, Cathleen; Adomßent, Maik; Seifert, Andreas; Schütz, Julia; Gunkel, Marjaana (Bildung und Hochschule. Impulse für Studium und Lehre am Beispiel des Leuphana College.)

Embodied Language Learning and Cognitive Bootstrapping: Methods and Design Principles - Lyon, Caroline; Nehaniv, Chrystopher L.; Saunders, Joe; Belpaeme, Tony; Bisio, Ambra; Fischer, Kerstin; Forster, Frank; Lehmann, Hagen; Metta, Giorgio; Mohan, Vishwanathan; Morse, Anthony; Nolfi, Stefano; et al. (International Journal of Advanced Robotic Systems)
Co-development of action, conceptualization and social interaction mutually scaffold and support each other within a virtuous feedback cycle in the development of human language in children. Within this framework, the purpose of this article is to bring together diverse but complementary accounts of research methods that jointly contribute to our understanding of cognitive development and in particular, language acquisition in robots. Thus, we include research pertaining to developmental robotics, cognitive science, psychology, linguistics and neuroscience, as well as practical computer science and engineering. The different studies are not at this stage all connected into a cohesive whole; rather, they are presented to illuminate the need for multiple different approaches that complement each other in the pursuit of understanding cognitive development in robots. Extensive experiments involving the humanoid robot iCub are reported, while human learning relevant to developmental robotics has also contributed useful results. Disparate approaches are brought together via common underlying design principles. Without claiming to model human language acquisition directly, we are nonetheless inspired by analogous development in humans and consequently, our investigations include the parallel co-development of action, conceptualization and social interaction. Though these different approaches need to ultimately be integrated into a coherent, unified body of knowledge, progress is currently also being made by pursuing individual methods.
Keywords: Robot Language; Human Robot Interaction; HRI; Developmental Robotics; Cognitive Bootstrapping; Statistical Learning

Effekte von Objekt-Familiarisierung auf die frühe gestische Kommunikation. Individuelle Unterschiede in Hinblick auf den späteren Wortschatz - Grimminger, Angela; Lüke, Carina; Ritterfeld, Ute; Liszkowski, Ulf; Rohlfing, Katharina (Frühe Bildung)
There is ongoing discussion on the function of the early production of gestures with regard to whether they reduce children's cognitive demands and free their capacity to perform other tasks (e.g., Goldin-Meadow & Wagner, 2005) or whether young children point in order to share their interest or to elicit information from their caregivers (e.g., Begus & Southgate, 2012; Liszkowski, Carpenter, Henning, Striano & Tomasello, 2004). The different assumptions lead to diverse predictions regarding infants' gestural or multimodal behavior in recurring situations, in which some objects are familiar and others are unfamiliar. To examine these different predictions, we observed 14 children aged between 14 and 16 months biweekly in a semi-experimental situation with a caregiver and explored how children's verbal and gestural behaviors change as a function of their familiarization with objects. We split the children into two groups based on their reported vocabulary size at 21 months of age (larger vs. smaller vocabulary). We found that children with a larger vocabulary at 21 months had an increase in their pointing with words toward unfamiliar objects as well as in their total amount of words, whereas for children with smaller vocabularies we did not find differences in relation to their familiarization with objects. We discuss these findings in terms of a social-pragmatic use of pointing gestures.
Keywords: gesture; pointing; familiarity; individual differences

An Alternative to Mapping a Word onto a Concept in Language Acquisition: Pragmatic Frames - Rohlfing, Katharina; Wrede, Britta; Vollmer, Anna-Lisa; Oudeyer, Pierre-Yves (FRONTIERS IN PSYCHOLOGY)
The classic mapping metaphor posits that children learn a word by mapping it onto a concept of an object or event. However, we believe that a mapping metaphor cannot account for word learning, because even though children focus attention on objects, they do not necessarily remember the connection between the word and the referent unless it is framed pragmatically, that is, within a task. Our theoretical paper proposes an alternative mechanism for word learning. Our main premise is that word learning occurs as children accomplish a goal in cooperation with a partner. We follow Bruner's (1983) idea and further specify pragmatic frames as the learning units that drive language acquisition and cognitive development. These units consist of a sequence of actions and verbal behaviors that are co-constructed with a partner to achieve a joint goal. We elaborate on this alternative, offer some initial parametrizations of the concept, and embed it in current language learning approaches.
Keywords: language acquisition; pragmatics; infants' social learning; frames; learning and memory; developmental robotics

Preschoolers' engagement in social interaction with an autonomous robotic system - Lücking, Phillip; Rohlfing, Katharina; Wrede, Britta; Schilling, Malte (2016 Joint IEEE International Conference on Development and Learning and Epigenetic Robotics (ICDL-EpiRob))

Einstellungen zur Inklusion im Zusammenhang mit der Motivation für die Beschäftigung mit inklusionsspezifischen Fragestellungen bei Studentinnen und Studenten des Lehramts an Grundschulen. Vortrag auf der 4. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF) - Görel, Gamze; Hellmich, Frank; Schwab , Susanne

Rückmeldungen zu Leseprozessen in Elternhaus und Schule im Zusammenhang mit der Lesemotivation von Kindern im dritten und vierten Grundschuljahr. Vortrag auf der 4. Tagung der Gesellschaft für Empirische Bildungsforschung (GEBF) - Hellmich, Frank; Hoya, Fabian Karl

Einstellungen zum inklusiven Unterricht bei Lehrkräften als Voraussetzungen für inklusives Lernen in der Grundschule. Vortrag auf dem 25. Kongress der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) - Görel, Gamze; Hellmich, Frank

Primary school children`s attitudes towards peers with special educational needs - Löper, Marwin Felix; Görel, Gamze; Pfahl, Rebecca; Hellmich, Frank

Primary school teachers` attitudes towards inclusion and their interest in inclusive teaching - Görel, Gamze; Hellmich, Frank

Leseleistungen von Kindern im Grundschulalter im Zusammenhang mit den Rückmeldungen ihrer Lehrerinnen und Lehrer im Leseunterricht der Grundschule – Ergebnisse aus einer Mehrebenenanalyse. Vortrag auf der 25. Jahrestagung „Profession und Disziplin – Grundschulpädagogik im Diskurs“ der Kommission Grundschulforschung und Pädagogik der Primarstufe (Sektion Schulpädagogik) der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) - Hoya, Fabian Karl; Hellmich, Frank

Motivation und Einstellungen zur Inklusion bei deutschen und österreichischen Studentinnen und Studenten mit dem Studienschwerpunkt Grundschule – ein Vergleich. Vortrag auf der 25. Jahrestagung „Profession und Disziplin – Grundschulpädagogik im Diskurs“ der Kommission Grundschulforschung und Pädagogik der Primarstufe (Sektion Schulpädagogik) der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) - Görel, Gamze; Hellmich, Frank; Schwab, Susanne

Bedingungsfaktoren für Einstellungen von Grundschulkindern gegenüber Peers mit sonderpädagogischem Förderbedarf. Vortrag auf der 25. Jahrestagung „Profession und Disziplin – Grundschulpädagogik im Diskurs“ der Kommission Grundschulforschung und Pädagogik der Primarstufe (Sektion Schulpädagogik) der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE) - Löper, Marwin Felix; Görel, Gamze; Pfahl, Rebecca; Hellmich, Frank

The role of pre-service teachers` attitudes towards inclusion for their motivation to engage in inclusive educational issues during their studies. Vortrag im Rahmen des Symposiums "Teachers' self-efficacy beliefs, attitudes and motivation to engage in inclusive education" (Chair: Marco Hessels). ECER 2016 (European Conference on Educational Research) - Hellmich, Frank; Görel, Gamze; Schwab, Susanne

The role of primary school students`perceptions of their parental and teachers` feedback for their reading motivation. Vortrag auf der ECER 2016 (European Conference on Educational Research). „Leading Education: The Distinct Contributions of Educational Research and Researchers" - Hoya, Fabian Karl; Hellmich, Frank

Towards a quantum interface between telecommunication and UV wavelengths: design and classical performance - Rütz, Helge; Luo, Kai-Hong; Suche, Hubertus; Silberhorn, Christine (Applied Physics B)

A versatile design for resonant guided-wave parametric down-conversion sources for quantum repeaters - Brecht, Benjamin; Luo, Kai Hong; Herrmann, Harald; Silberhorn, Christine (Applied Physics B)

Hardy–Stein identities and square functions for semigroups - Bañuelos, Rodrigo; Bogdan, Krzysztof; Luks, Tomasz (Journal of the London Mathematical Society)
Keywords: General Mathematics

Kohäsion und soziales Kapital : Ausschließungsprozesse in der Sozialen Arbeit - Landhäußer, Sandra (Sozialmagazin)
Soziale Arbeit rückt im Zusammenhang mit der Thematisierung eines geringen gesellschaftlichen Zusammenhalts in den Vordergrund, wenn vermehrte Kohäsion mit der Aktivierung sozialen Kapitals erreicht werden soll. Vor diesem Hintergrund wird eine auf politischer Ebene prominente Version sozialen Kapitals sowie ihr Beitrag zur Erhöhung gesellschaftlichen Zusammenhalts genauer untersucht und auf seine Aussagekraft für die Soziale Arbeit hin befragt.

Simulations of high harmonic generation from plasmonic nanoparticles in the terahertz region - Grynko, Yevgen; Zentgraf, Thomas; Meier, Torsten; Förstner, Jens (Applied Physics B)
Keywords: tet_topic_meta; tet_topic_shg

Detection of cyclostationarity in the presence of temporal or spatial structure with applications to cognitive radio - Pries, Aaron; Ramírez, David; Schreier, Peter J. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)
One approach to spectrum sensing for cognitive radio is the detection of cyclostationarity. We extend an existing multi-antenna detector for cyclostationarity proposed by Ramírez et al. [1], which makes no assumptions about the noise beyond being (temporally) wide-sense stationary. In special cases, the noise could be uncorrelated among antennas, or it could be temporally white. The performance of a general detector can be improved by making use of a priori structural information. We do not, however, require knowledge of the exact values of the temporal or spatial noise covariances. We develop an asymptotic generalized likelihood ratio test and evaluate the performance by simulations.

Flag-based detection of weak gas signatures in long-wave infrared hyperspectral image sequences. - Marrinan, Tim; Beveridge, J. Ross; Draper, Bruce; Kirby, Michael; Peterson, Chris (SPIE Defense, Security, and Sensing)

A unified scheme to achieve the degrees-of-freedom region of the MIMO interference channel with delayed channel state information - Rezaee, Mohsen; Schreier, Peter J.; Guillaud, M.; Clerckx, B. (IEEE Trans.\ Comm.)

Analysis of the downlink saturation throughput of an asymmetric IEEE 802.11 n-based WLAN - Soleymani, Mohammad; Maham, Behrouz; Ashtiani, Farid (Proc. IEEE International Conference on Communications (ICC))

Sample-poor estimation of order and common signal subspace with application to fusion of medical imaging data - Levin-Schwartz, Y.; Song, Yang; Schreier, Peter J.; Calhoun, V.D.; Adali, Tülay (NeuroImage)

Cross-validation techniques for determining the number of correlated components between two data sets when the number of samples is very small - Lameiro, Christian; Schreier, Peter J. (Proc.\ Asilomar Conf.\ Signals Syst.\ Computers)

Maximally improper interference in underlay cognitive radio networks - Lameiro, Christian; Santamaría, I.; Utschick, W.; Schreier, Peter J. (Proc.\ IEEE Int.\ Conf.\ Acoustics, Speech and Signal Process.)

Measurement-driven quality assessment of nonlinear systems by exponential replacement - Stein, Manuel; Nossek, Josef A.; Barbé, Kurt (Proc.\ IEEE Int. Instrum. & Meas. Tech.\ Conf.)

Analysis of the downlink saturation throughput of an asymmetric IEEE 802.11 n-based WLAN - Soleymani, Mohammad; Maham, Behrouz; Ashtiani, Farid (Proc. IEEE International Conference on Communications (ICC))

Rezension von Ernst Kapp: Grundlinien einer Philosophie der Technik. Über die Entstehung der Kulturgeschichte aus neuen Gesichtspunkten - Alpsancar, Suzana (Technikgeschichte)

Das Darmstädter Modell: Entwicklungspotentiale für die Interdisziplinaritäten in der Lehre - Alpsancar, Suzana; Denker, Kai; Gehring, Petra; Terizakis, Georgios; Abdelhamid, Michaela; Brenneis, Andreas; Grill, Annika; Frehe, Hardy; Tulatz, Kaja

Mode Macht Körper – wie die Materialität von Kleidung Modekörper und Körper definiert - Haller, Melanie; Villa, Paula-Irene; Schadler (Hg.), Corinna (Becoming with Things – Bodies, Objects, Practice, Themenheft der Zeitschrift Body Politics, Heft 9, 2016. Link: http://bodypolitics.de/de/das-aktuelle-heft/ (16.07.2017).)

Tango Argentino und seine Mode – Bewegungsfreiheiten und Kleiderordnungen - Haller, Melanie; Rieger (Hg.), Rita (Bewegungsfreiheit. Tanz als kulturelle Manifestation (1900-1950), Graz 2017.)

Can the CCCTB Alleviate Tax Discrimination against Loss-Making European Multinational Groups? - Ortmann, Regina; Sureth-Sloane, Caren (Journal of Business Economics)

Evaluation der Reflexion: Wissenschaftliche Begleitung eines Projekts zur Überprüfung eines semesterübergreifenden Begleitangebots auf spezifische Aspekte der Persönlichkeit. - Seifert, Andreas; Balsam, Rebecca; Newig, Jens (Professionalisierung der Hochschuldidaktik)

Can 28-month-old children learn spatial prepositions robustly from pictures? Yes, when narrative input is provided. - Rohlfing, Katharina; Nachtigäller, Kerstin (Frontiers in Language Science)

Analysis of individual and systematic determinants regarding arithmetic skills of first graders. - Seifert, Andreas; Eilerts, Katja; Rinkens, Hans-Dieter (13th International Congress on Mathematical Education (ICME).)

Der Einfluss individueller und institutioneller Faktoren auf die Kompetenzeinschätzung von Studierenden im Praxissemester. - Festner, Dagmar; Gröschner, Alexander; Seifert, Andreas (4. Tagung der Gesellschaft der Empirischen Bildungsforschung (GEBF))

Analysekompetenz – ein mehrdimensionales Konstrukt. - Scholl, Daniel; Seifert, Andreas (DGFE-Kongress „Räume für Bildung. Räume der Bildung.“)

Bühnenrollen und Identitätskonzepte: Karrierestrategien von Künstlerinnen im Theater des 19. Jahrhunderts

Stuttgarter Hoftheater und Hamburger Stadttheater: Institutionen der deutschsprachigen Theaterlandschaft zwischen regionaler Prägung und Kulturtransfer - Tumat, Antje (Bühne und Bürgertum, Das Hamburger Stadttheater 1770-1850)

Das Paderborner „Portfolio Praxiselemente“ AIMs auf dem Weg - Rotärmel, Tanja; Niestradt-Bietau, Ilsegret (Portfolioarbeit phasenübergreifend gestalten. Konzepte, Ideen und Anregungen aus der LehrerInnenbildung)

Global mobility policies, social positioning and boundary spanning work of expatriate managers - Mense-Petermann, Ursula; Spiegel, Anna

Verflochtene Mobilitäten und ihr Management. Mobilitätspraktiken von Expatriate-Managern und ihren ’trailing spouses’ im Auslandseinsatz - Spiegel, Anna; Mense-Petermann, Ursula (Österreichische Zeitschrift für Soziologie)
Der vorliegende Aufsatz behandelt die spezifischen Mobilitätsformen von Fach- und Führungskräften, die von ihren Unternehmen auf Zeit in eine ausländische Niederlassung entsandt werden, und die sie ermöglichende Mobilitäts- arbeit. Gezeigt wird, 1) dass es sich bei der Mobilität von Expatriates um komplexe verflochtene Mobilitäten handelt, die sich zu einer Hypermobilität verdichten, und 2) dass diese Hypermobilität konstitutiv auf die aktive Mobilitätsarbeit der mit reisenden Ehefrauen angewiesen ist. Damit wird deutlich, dass es sich hier um ein geschlechtsspezifisch strukturiertes Mobilitätsmanagement handelt. Die am Beispiel der Mobilität von Expatriates gewonnenen Befunde eröffnen auch neue theoretische Perspektiven für die Mobilitätsforschung insgesamt.

Lateral association and elongation of vimentin intermediate filament proteins: A time-resolved light-scattering study - Lopez, Carlos G.; Saldanha, Oliva; Huber, Klaus; Köster, Sarah (Proceedings of the National Academy of Sciences)
Significance The hierarchical assembly pathway of the cytoskeletal protein vimentin may be responsible for the astonishing mechanical properties of the emerging filaments, such as high flexibility and extensibility, and thus play a key role in cellular mechanics. A two-step assembly mechanism, involving a lateral and a subsequent elongational step, has been established; however, the elongational step could not be followed in solution. Here, we show direct in situ observation and modeling of the elongation reaction of the filaments on the relevant length and time scales, using time-resolved, multiangle static and dynamic light scattering. We thus achieve sufficient spatio-temporal resolution without the need of labeling, staining, or adsorption to substrates.
Keywords: Multidisciplinary

Insight into Fast Nucleation and Growth of Zeolitic Imidazolate Framework-71 by In Situ Time-Resolved Light and X-ray Scattering Experiments - Saha, Sanjib; Springer, Sergej; Schweinefuß, Maria E.; Pontoni, Diego; Wiebcke, Michael; Huber, Klaus (Crystal Growth & Design)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Contraction and Coagulation of Spherical Polyelectrolyte Brushes in the Presence of Ag+, Mg2+, and Ca2+ Cations - Ezhova, Anna; Huber, Klaus (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Systematic Limitations in Concentration Analysis via Anomalous Small-Angle X-ray Scattering in the Small Structure Limit - Goerigk, Guenter; Lages, Sebastian; Huber, Klaus (Polymers)
Keywords: Polymers and Plastics; General Chemistry

Loss of Resting-State Posterior Cingulate Flexibility Is Associated with Memory Disturbance in Left Temporal Lobe Epilepsy. - Douw, L; Leveroni, CL; Tanaka, N; Emerton, BC; Cole, AJ; Reinsberger, Claus; Stufflebeam, SM (PLoS One)

Bewegung und neurologische Erkrankungen - Barthel, Thorsten; van den Bongard, Franziska; Ströhlein, Julia Kristin; Reinsberger, Claus (Körperliche Aktivität und Gesundheit)

An integrated 118.4 to122 GHz low noise phase-locked loop (PLL) in 0.13 µm SiGe BiCMOS technology - Ali, U.; Bober, M.; Thiede, Andreas (2016 German Microwave Conference (GeMiC))

Photon Cascade from a Single Crystal Phase Nanowire Quantum Dot - Bavinck, M. Bouwes; Jöns, Klaus D.; Zielinski, M; Patriarche, G; Harmand, J-C; Akopian, N; Zwiller, V

Controlling the exciton energy of a nanowire quantum dot by strain fields - Chen, Y; Zadeh, I. Esmaeil; Jöns, Klaus D.; Fognini, A; Reimer, M.E; Zhang, J; Dalacu, D; Poole, P.J; Ding, F; Zwiller, V; Schmidt, O.G

Deterministic Integration of Single Photon Sources in Silicon Based Photonic Circuits - Zadeh, I.Esmaeil; Elshaari, A.W; Jöns, Klaus D.; Fognini, A; Dalacu, D; Poole, P.J; Reimer, M.E; Zwiller, V

Thermo-optic characterization of silicon nitride resonators for cryogenic photonic circuits - Elshaari, A.W; Zadeh, I. Esmaeil; Jӧns, Klaus D.; Zwiller, V

Konzeptentwicklung zur Einbindung von Simulationen - Unterstützung des Informationsmanagements im Bereich der zivilen Gefahrenabwehr - Schneider, Steffen

Molecular modeling and simulation for industrial applications - Miroshnichenko, Svetlana

Shaped Gaussian Dictionaries for Quantized Networked Control Systems with Correlated Dropouts - Peters, E. G. W.; Quevedo, D. E.; stergaard, J. (Trans. Signal Processing)

Maximum Hands-Off Control: A Paradigm of Control Effort Minimization - Nagahara, M.; Quevedo, D. E.; Nešić, D. (Trans. Automat. Contr.)

Multiple Descriptions for Packetized Predictive Control - stergaard, J.; Quevedo, D. E. (EURASIP J. Adv. Signal Processing)

Controller and scheduler codesign for feedback control over IEEE 802.15.4 networks - Peters, E. G. W.; Quevedo, D. E.; Fu, M. (Trans. Contr. Syst. Technol.)

Discrete-time hands-off control by sparse optimization - Nagahara, M.; stergaard, J.; Quevedo, D. E. (EURASIP J. Adv. Signal Processing)

Robust stability of a class of Networked Control Systems - Lješnjanin, M.; Nešić, D.; Quevedo, D. E. (Automatica)

Kalman Filtering With Relays Over Wireless Fading Channels - Leong, A. S.; Quevedo, D. E. (Trans. Automat. Contr.)

Characterization of maximum hands-off control - Chatterjee, D.; Nagahara, M.; Quevedo, D. E.; Rao, K. S. M. (Syst. & Contr. Lett.)

Predictive control, embedded cyberphysical systems and systems of systems – A perspective - Lucia, S.; Kögel, M.; Zometa, P.; Quevedo, D. E.; Findeisen, R. (Annual Reviews in Control)

On Network Topology Reconfiguration for Remote State Estimation - Leong, A. S.; Quevedo, D. E.; Ahlén, A.; Johansson, K. H. (Trans. Automat. Contr.)

Mehrphasige ph ̈anomenologische sowie mehrskalige mikroskopische Modellierung von Phasenumwandlungen in einem Hybridumformprozess - Schneidt, Andreas

Rezension zu Brinkmann, Erika (Hrsg.): Rechtschreiben in der Diskussion. Schriftspracherwerb und Rechtschreibunterricht (= Beiträge zur Reform der Grundschule 140) Bad Langensalza: Beltz. 318 S. - Blachut, Alisa (Grundschulunterricht Deutsch)

Plants as Digital Things - Alpsancar, Suzana (Tecnoscienza. Italian Journal of Science & Technology Studies)
Seeds have traditionally been collected according to their reproductive cycles, i.e. the time when they lose their potential of becoming a real plant. Therefore, the locations of botanic gardens or seed banks imply the vicinity of agricultural land. This article exemplifies the transformation of plant collections into gene and data banks by investigating the Svalbard Global Seed Vault (SGSV) in Norway and the German Genebank for Fruit Crops (DGO). It shows that international efforts to safeguard biodiversity by intertwining them with bioinformatics infrastructure transform seeds and other plant genetic material into digitalized objects. The almost virtual genetic material, now stored without the neighborhood of acres or gardens, is, at the same time, seen as “options” for new high-tech plants, which might be transplanted to a future territory. Consequently, plant varieties are circulating around the globe in form of genetic material and data. The article shows that the digitalization induces a specific distinction between the material and the digital flows of plants.

Einfluss von Mixed-Mode-Beanspruchung auf das Ermüdungsrisswachstum in Bauteilen und Strukturen - Eberlein, Alexander

A Linear Time Algorithm for Quantum 2-SAT - de Beaudrap, Niel; Gharibian, Sevag (Proceedings of the 31st Conference on Computational Complexity (CCC 2016))
The Boolean constraint satisfaction problem 3-SAT is arguably the canonical NP-complete problem. In contrast, 2-SAT can not only be decided in polynomial time, but in fact in deterministic linear time. In 2006, Bravyi proposed a physically motivated generalization of k-SAT to the quantum setting, defining the problem "quantum k-SAT". He showed that quantum 2-SAT is also solvable in polynomial time on a classical computer, in particular in deterministic time O(n^4), assuming unit-cost arithmetic over a field extension of the rational numbers, where n is number of variables. In this paper, we present an algorithm for quantum 2-SAT which runs in linear time, i.e. deterministic time O(n+m) for n and m the number of variables and clauses, respectively. Our approach exploits the transfer matrix techniques of Laumann et al. [QIC, 2010] used in the study of phase transitions for random quantum 2-SAT, and bears similarities with both the linear time 2-SAT algorithms of Even, Itai, and Shamir (based on backtracking) [SICOMP, 1976] and Aspvall, Plass, and Tarjan (based on strongly connected components) [IPL, 1979].
Keywords: quantum 2-SAT; transfer matrix; strongly connected components; limited backtracking; local Hamiltonian

Entwicklung einer Methodik zur Simulation der Lebensdauer von Klebverbindungen mit Polyurethan-Klebstoffen - Kaßner, Martin

Qualifizierung des Reibelementschweißens von ultrahochfesten Aluminium-Silizium-beschichteten Stahlblechwerkstoffen für den Karosseriemischbau - Olfermann, Thomas Ernst Christian

Qualifizierung von PU-Klebstoffen für den Einsatz auf lackierten Oberflächen (semi-)struktureller und crashrelevanter Strukturen eines Automobils - Beck, Alexander

Entwicklung eines impulsartig und butzenfrei eingetriebenen Elementes für das Widerstandsschweißen von Aluminium-Stahl-Verbindungen - Hartwig-Biglau, Sergej

Weiterentwicklung der mechanischen Fügetechnik zum vorlochfreien Fügen von Faser-Kunststoff-Verbunden im Automobilkarosseriebau - Rothe, Kevin

Beitrag zur experimentellen und simulativen Beschreibung der Delaminations-Initiierung an bauteilnahen Faserverbund-Geometrien - Frede, Daniel

Weiterentwicklung des Widerstandselementschweißens für den Einsatz in der automobilen Serienfertigung - Meyer, Christoffer

Critical Theory of Communication: New Readings of Lukács, Adorno, Marcuse, Honneth and Habermas in the Age of the Internet - Fuchs, Christian

Reading Marx in the Information Age. A Media and Communication Studies Perspective on Capital Volume 1 - Fuchs, Christian

Sosyal Medya: Eleştirel Bir Giriş - Fuchs, Christian

Are number fields determined by Artin L-functions? - Klüners, Jürgen; Nicolae, Florin (Journal of Number Theory)
Let k be a number field, K/k a finite Galois extension with Galois group G, χ a faithful character of G. We prove that the Artin L-function L(s,χ,K/k) determines the Galois closure of K over $\ℚ$. In the special case $k=\ℚ$ it also determines the character χ.
Keywords: Algebra and Number Theory

Einzeltropfen in Flüssig-flüssig-Systemen: Numerische Untersuchungen zu Fluiddynamik, Stofftransport und Marangonikonvektion - Engberg, Roland

Investigation of transport phenomena in systems with complex geometry using computational fluid dynamics - Atmakidis, Theodoros

Theoretische und experimentelle Untersuchung der Strömungs- und Transportvorgänge von Anstaupackungen - Yildirim, Ömer

Marx and the political economy of the media. Studies in critical social sciences. Volume 79

Marx in the age of digital capitalism. Studies in critical social sciences, Volume 80

马克思归来 (Marx is Back)

Lavoro digitale e imperialismo - Fuchs, Christian (Sinistrainrete)

Racism, Nationalism and Right-Wing Extremism Online: The Austrian Presidential Election 2016 on Facebook - Fuchs, Christian (Momentum Quarterly – Zeitschrift für sozialen Fortschritt (Journal for Societal Progress))

Georg Lukács as a Communications Scholar: Cultural and Digital Labour in the Context of Lukács’ Ontology of Social Being - Fuchs, Christian (Media, Culture & Society)

Baidu, Weibo and Renren: The Global Political Economy of Social Media in China - Fuchs, Christian (Asian Journal of Communication)

Dallas Smythe Today – The Audience Commodity, the Digital Labour Debate, Marxist Political Economy and Critical Theory. Prolegomena to a Digital Labour Theory of Value - Fuchs, Christian (Marx and the political economy of the media)

Critical Theory - Fuchs, Christian (International Encyclopedia of Communication Theory and Philosophy)

Critical Theory of Communication as Critical Sociology of Critique in the Age of Digital Capitalism: A Response to Jan Løhmann Stephensen's Rview Essay on Culture and Economy in the Age of Social Media - Fuchs, Christian (Conjunctions: Transdisciplinary Journal of Cultural Participation)

Henryk Grossmann 2.0: A Critique of Paul Mason’s Book “PostCapitalism: A Guide to Our Future“ - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

When Will Greece Get its Money Back from Germany? Reflections on Yanis Varoufakis’ New Book - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

Capitalism Today: The Austrian Presidential Election and the State of the Right and the Left in Europe - Fuchs, Christian (LSE Euro Crisis in the Press-blog)

Paul Mason sur le postcapitalisme: Henryk Grossmann version 2.0 - Fuchs, Christian (Études Marxistes)